2009
DOI: 10.1002/chin.200947031
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: Dzhemilev Reaction in the Synthesis of Five‐Membered Sulfur and Selenium Heterocycles.

Abstract: Ring closure reactions O 0130Dzhemilev Reaction in the Synthesis of Five-Membered Sulfur and Selenium Heterocycles. -Cyclometalation of allenes like (I) and (V), alkynes like (VIII) or simple alkenes with organoaluminum or organomagnesium reagents, followed by reaction with elemental sulfur or selenium, provides a one-pot access to a variety of thiophene or selenophene derivatives. -(D'YAKONOV*, V. A.; IBRAGIMOV, A. G.; KHALILOV, L. M.; MAKAROV, A. A.; TIMERKHANOV, R. K.; TUKTAROVA, R. A.; TRAPEZNIKOVA, O. A.;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…Commercially available EtAlCl 2 (92%), Et 2 AlCl (87%), i-BuAlCl 2 (90%) (Redkino Pilot-Production Plant), AlCl 3 , and Cp 2 TiCl 2 (Aldrich) were used. Compounds V-X were identified by comparing with authentic samples [2,7,8].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Commercially available EtAlCl 2 (92%), Et 2 AlCl (87%), i-BuAlCl 2 (90%) (Redkino Pilot-Production Plant), AlCl 3 , and Cp 2 TiCl 2 (Aldrich) were used. Compounds V-X were identified by comparing with authentic samples [2,7,8].…”
Section: Methodsmentioning
confidence: 99%
“…
Intermolecular cycloalumiation of cyclic 1,2-dienes and ethylene with organoaluminum compounds R n AlCl 3 -n in the presence of zirconium-and titanium-based catalysts occurred regioselectively with formation of unsaturated bicyclic organoaluminum compounds in high yields.[Zr] = Cp 2 ZrCl 2 .We previously [1,2] showed that catalytic cycloalumination of cyclic 1,2-dienes with Et 3 Al or joint cycloalumination of cyclic 1,2-dienes and terminal olefins with EtAlCl 2 in the presence of Cp 2 ZrCl 2 as catalyst resulted in the formation of bicyclic organoaluminum compounds (Scheme 1). With a view to extend the scope of the above reactions and develop new efficient procedures for the synthesis of bicyclic organoaluminum compounds, as well as to replace extremely pyrophoric Et 3 Al by less fire-hazardous alkylhaloalanes, we examined joint cycloalumination of cyclic 1,2-dienes and ethylene in the presence of R n AlCl 3 -n , metallic magnesium, and catalysts based on titanium and zirconium complexes.

We initially used a procedure developed by us previously for the synthesis of cyclic organoaluminum compounds on the basis of cycloalumination of olefins and acetylenes with EtAlCl 2 generated from 1,2-dichloroethane and activated magnesium [3−6].

…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…In contrast to the cyclomagnesation of cyclic and acyclic 1,2-dienes, the catalytic cycloalumination of 1,2-cyclononadiene using AlEt 3 in the presence of Cp 2 ZrCl 2 leads with high selectivity to bicyclic aluminacyclopentane 21 [25], whose reaction in situ with S 8 at 60°C gives 12-thiabicyclo[7.3.0 1,9 ]dodec-1(2)-ene (22) …”
mentioning
confidence: 96%
“…According to published data, disubstituted acetylenes react with Et 3 Al in the presence of Cp 2 ZrCl 2 to give 2,3-dialkyl(aryl)aluminacyclopent-2-enes in ~90% yield [1−3]; the products are exceptionally interesting as intermediate products in the development of one-pot procedures for the synthesis of substituted cyclopentenones [4,5], cyclopropanes [6−9], and some other difficultly accessible carbo-and heterocyclic compounds [10] (Scheme 1).…”
mentioning
confidence: 99%